PENERAPAN METODE BERCERITA ISLAMI PADA PEMBELAJARAN ONLINE DI RA ASSA’IDIYYAH KARANGPLOSO (Jurnal Dewantara, 2021)
The COVID-19 pandemic has had an impact on all walks of life, especially in the world of early childhood education. As a result of the COVID-19 pandemic, the teaching and learning process is carried out at home through a distance learning process. One of the appropriate methods used in online learning at RA Assa'idiyyah during the pandemic is the Islamic storytelling method. The research was conducted using a qualitative approach in the form of a case study. Data collection techniques were carried out by means of observation, interviews, and documentation. learning activities based on themes that have been planned or arranged. The results of the research show that the delivery of the story content is adjusted to the theme at the time and contains Islamic values. Evaluation of the assessment of the level of achievement of students is very visible in the fields of developing religious and moral values, social emotional, and language, which can develop according to expectations and well.